Letter (copy) : Foodstuffs for Spain - Tewson, Vincent
029-0049-001 HVT/FC/150. Secretary's. 10th January, 1938. Mr. W. Schevenels, The International Federation of Trade Unions, 9, Avenue D'Orsay, PARIS, VIIe. Dear Schevenels, FOODSTUFFS FOR SPAIN Many thanks for your letter of the 8th instant which certainly clarifies the position in regard to the distribution of consignments sent to Spain from the International Solidarity Fund. It will of course be extremely helpful to receive a report in regard to what is happening to the goods sent, and I note that you intend writing me further when you receive a reply to your request for information from Spain. Yours sincerely, Assistant Secretary. 292/946/29/49